Adhesive-Bonded Joint Influence on Deflection of Composite Steel and Concrete Beams with Strengthening by External Steel Reinforcement - Davydenko, Yurii; Horb, Oleksandr; Avramenko, Yurii (International Journal of Engineering and Technology, 2018)
This paper presents experimental and theoretical research for calculating of composite steel and concrete beams deflection strengthened bonded steel plates. The use of epoxy-bonded plates to strengthen existing or damaged reinforced or composite steel beams concrete beams has been extensively researched. It has been proven to be a useful and reliable method of increasing the ultimate flexural capacity of both damaged and undamaged members. The actual deflection behavior in beams is probabilistic in nature and requires statistical methods for a rational analysis.Â Â